Temperature-tunable time-dependent snapping of viscoelastic metastructures with snap-through instabilities. (October 2019) - Che, Kaikai; Rouleau, Michael; Meaud, Julien
Abstract: 3D-printed metastructures and metamaterials with snap-through instabilities have been extensively investigated in recent years. However, most of the previous research has been limited to the analysis of their elastic response. This paper focuses on the time-dependent mechanics of 3D-printed viscoelastic metastructures with snap-through instabilities. Due to viscoelastic relaxation, a regime called pseudo-bistability can be observed: a previously deformed 3D-printed metastructure can appear to be temporarily bistable before snapping back to its undeformed configuration after a critical time. Experiments with 3D-printed samples and finite element simulations demonstrate that the critical time can be tuned by adjusting the temperature. While the time-dependent snapping causes a change in the overall height in the case of single layer metastructure, experimental and finite element results show that the same type of time-dependent snapping can also be used to obtain an internal reconfiguration when the overall height of a multilayer metastructure is constrained to remain constant. Because of the possibility of tuning the critical time for a given sample by varying the external temperature, harnessing the pseudo-bistable mechanics of these viscoelastic metastructures gives new opportunities towards the development of novel reconfigurable metastructures with programmable response and properties for applications in soft robotics or impact protection.